Disparities in Workplace Hazards and Organizational Protection Resources by Enterprise Size: A National Representative Study of South Korean Manufacturing Workers - Hye-Lin Lee; Ji-Hwan Kim; Taesun Kang; Garin Lee; Hayoung Lee; Hee Won Kim; Seung-Sup Kim (Elsevier, 2024)
Background: This study aimed to identify the prevalence of workplace hazards and organizational protection resources according to the size of the enterprise in the manufacturing industry of the Republic of Korea. Methods: We analyzed data of waged workers (weighted N = 5,879) from the Fifth Korean Working Conditions Survey (2017). Enterprise sizes were categorized as "micro enterprises" (less than five employees), "small enterprises" (5-49 employees) and "medium-large enterprises" (50 or more employees). Self-reported exposure to 18 physical, chemical, ergonomic, and psychological hazards were measured. The presence of organizational protection resources such as a labor union, a safety delegate working at the company, designated spaces to deal with safety, and the provision of health and safety information was evaluated. Results: Compared to workers in medium-large enterprises, those in micro enterprises showed a higher proportion of exposure to most of physical, chemical, ergonomic, and psychological hazards, except for exposure to solvents, prolonged sitting, and experiencing a state of emotional unrest. On the other hand, workers in micro enterprises had the lowest proportion of access to organizational protection resources. Conclusion: Our study demonstrates that manufacturing workers at the micro enterprise in the Republic of Korea are exposed to the most hazardous work environment and yet have access to the fewest organizational protection resources.